الجملة الاسمية المثبتة ودلالاتها النسقية في الربع الأخير من القرآن الكريم - سليم, أحمد محمد; كريم, هيوا عبدالله (Sulaimani Journal for Humanities, 2021)
This research, tagged with (the proven nominal sentence and its systemic implications in the last quarter of the Holy Qur’an - selected models), deals with the semantics of the nominal sentence pattern in the Holy Quran through the formulation of the nominal sentence in the present of abstract and emphatic proof, relying on multiple forms and patterns. Given the importance of this topic, the study came as an application to the last quarter of the Noble Qur’an; To reveal the manifestations of the grammatical system in it, as well as to find the connotations contained in the nominal sentence installed in different grammatical contexts. The research includes a study: (the affirmative nominal sentence, and the emphatic affirmative nominal sentence), a theoretical and applied study at the same time.
Keywords: Agreement; Syntactic agreement; the meaning of agreement